Environmental Aesthetics : Crossing Divides and Breaking Ground - Drenthen, Martin, 1966- (Book collections on Project MUSE., 2014)
Environmental aesthetics crosses several commonly recognized divides: between analytic and continental philosophy, Eastern and Western traditions, universalizing and historicizing approaches, and theoretical and practical concerns. This volume sets out to show how these, perspectives can be brought into conversation with one another. The first part surveys the development of the field and discusses some important future directions. The second part explains how widening the scope of environmental aesthetics demands a continual rethinking of the relationship between aesthetics and other fields. H.